Anti‐inflammatory effects of miR‐21 in the macrophage response to peritonitis. Issue 2 (17th September 2015) - Barnett, Rebecca Elise; Conklin, Daniel J.; Ryan, Lindsey; Keskey, Robert C.; Ramjee, Vikram; Sepulveda, Ernesto A.; Srivastava, Sanjay; Bhatnagar, Aruni; Cheadle, William G.
Abstract : MiRNA‐21 is beneficial in survival following induction of peritonitis with LPS by limiting the pro‐inflammatory phase of the innate response. Abstract : We investigated the role of microRNA‐21 in the macrophage response to peritonitis; microRNA‐21 expression increases in peritoneal macrophages after lipopolysaccharide stimulation but is delayed until 48 hours after cecal ligation and puncture. MicroRNA‐21–null mice and bone marrow–derived cell lines were exposed to cecal ligation and puncture or lipopolysaccharide, and survival, microRNA‐21 levels, target messenger RNAs and proteins, and cytokines were assayed. Macrophages were also transfected with microRNA‐21 mimics and antagomirs, and similar endpoints were measured. Survival in microRNA‐21–null mice was significantly decreased after lipopolysaccharide‐induced peritonitis but unchanged after cecal ligation and puncture compared with similarly treated wild‐type mice. MicroRNA‐21 expression, tumor necrosis factor‐α, interleukin 6, and programmed cell death protein 4 levels were increased after lipopolysaccharide addition in peritoneal cells. Pelino1 and sprouty (SPRY) messenger RNAs were similarly increased early, whereas programmed cell death protein 4 messenger RNA was decreased after lipopolysaccharide, and all microR‐21 target messenger RNAs were subsequently decreased by 24 hours after lipopolysaccharide. Transfection with mimics and antagomirs led to appropriate responses in microRNA‐21 and tumor necrosis factor‐α. Knockdown of microRNA‐21 in bone marrow–derived cells showed increased tumor necrosis factor‐α and decreased interleukin 10 in response to lipopolysaccharide. Target proteins were unaffected by knockdown as was extracellular signal‐regulated kinase; however, the nuclear factor κB p65 subunit was increased after lipopolysaccharide in the microRNA‐21 knockout cells. In contrast, there was little change in these parameters after cecal ligation and puncture induction between null and wild‐type mice. MicroRNA‐21 is beneficial to survival in mice following lipopolysaccharide peritonitis. Overexpression of microRNA‐21 decreased tumor necrosis factor‐α secretion, whereas suppression of microRNA‐21 expression increased tumor necrosis factor‐α and interleukin 6, and decreased interleukin 10 levels after lipopolysaccharide. Protein targets of microRNA‐21 were not different following suppression of microRNA‐21. Nuclear factor κB was increased by suppression of microRNA‐21. These findings demonstrate microRNA‐21 is beneficial in modulating the macrophage response to lipopolysaccharide peritonitis and an improved understanding of the anti‐inflammatory effects of microRNA‐21 may result in novel, targeted therapy against peritonitis and sepsis.